Stabilitas Imunoglobulin M (IgM) Campak pada Dried Serum Spots - Puspa, Kartika Dewi; Mursinah, Mursinah; Budianto, Ratumas Rosmawati (Jurnal Kefarmasian Indonesia, 2013)
Shipping and storage of measles serum specimens from fields to the reference laboratory must consider the cold chain in order to maintain the stability of immunoglobulin M (IgM) in serum. Meanwhile, to maintain the cold chain needs special handling. This study aimed to determine the use of filter paper as an alternative in shipping and storage of specimens. This experimental study used measles positive serum received at the National Measles Laboratory Center for Biomedical and Basic Technology of Health from January until March 2011. There were three groups of sample. Each group consisted of 9 specimens. The effects of temperature and storage period on the stability of measles IgM of dried serum spots (DSS) stored in 4ºC and 25ºC for one, three, six, nine, twelve, and five teen days were tested at the National Measles Laboratory Center for Biomedical and Basic Technology of Health from July until December 2011. The stability of measles IgM of DSS that were stored at 4ºC and 25ºC temperature showed no significant difference (p = 0.316) compared to the serums stored at a temperature of 4ºC in the measurements on the third day. Dried serum spots can not be used as sample alternative for detection of measles virus-spesific immunoglobulin M